Synergistic Effect of Bypassing Agents and Sequence Identical Analogue of Emicizumab and Fibrin Clot Structure in the In Vitro Model of Hemophilia A - Zong, Yanan; Antovic, Aleksandra; Soutari, Nida Mahmoud Hourani; Antovic, Jovan; Pruner, Iva (TH Open, 2020)
Development of inhibitors to factor VIII (FVIII) occurs in approximately 30% of severe hemophilia A (HA) patients. These patients are treated with bypassing agents (activated prothrombin complex concentrate [aPCC] and recombinant activated FVII-rFVIIa). Recently, a bispecific FIX/FIXa- and FX/FXa-directed antibody (emicizumab) has been approved for the treatment of HA patients with inhibitors. However, the data from clinical studies imply that coadministration of emicizumab and bypassing agents, especially aPCC, could have a thrombotic effect.This study was aimed to address the question of potential hypercoagulability of emicizumab and bypassing agents' coadministration, we have investigated fibrin clot formation and structure in the in vitro model of severe HA after adding sequence-identical analogue (SIA) of emicizumab and bypassing agents.Combined overall hemostasis potential (OHP) and fibrin clot turbidity assay was performed in FVIII-deficient plasma after addition of different concentrations of SIA, rFVIIa, and aPCC. Pooled normal plasma was used as control. The fibrin clots were analyzed by scanning electron microscopy (SEM).OHP and turbidity parameters improved with the addition of aPCC, while therapeutic concentrations of rFVIIa did not show substantial improvement. SIA alone and in combination with rFVIIa or low aPCC concentration improved OHP and turbidity parameters and stabilized fibrin network, while in combination with higher concentrations of aPCC expressed hypercoagulable pattern and generated denser clots.Our in vitro model suggests that combination of SIA and aPCC could potentially be prothrombotic, due to hypercoagulable changes in fibrin clot turbidity and morphology. Additionally, combination of SIA and rFVIIa leads to the formation of stable clots similar to normal fibrin clots.
Keywords: emicizumab; bypassing agents; fibrin clot; hemophilia A